Thinking about Life - Agutter, Paul S. author. aut Link
XIV, 267 p.
Keywords: Our previous book, About Life, concerned modern biology. We used our present-day understanding of cells to ‘define’ the living state, providing a basis for exploring several general-interest topics: the origin of life, extraterrestrial life, intelligence, and the possibility that humans are unique. The ideas we proposed in About Life were intended as starting-points for debate – we did not claim them as ‘truth’ – but the information on which they were based is currently accepted as ‘scientific fact’. What does that mean? What is ‘scientific fact’ and why is it accepted? What is science – and is biology like other sciences such as physics (except in subject m- ter)? The book you are now reading investigates these questions – and some related ones. Like About Life, it may particularly interest a reader who wishes to change career to biology and its related subdisciplines. In line with a recommendation by the British Association for the Advancement of Science – that the public should be given fuller information about the nature of science – we present the concepts underpinning biology and a survey of its historical and philosophical basis.